A rare clinical finding of mandibular distomolar at Aminu Kano Teaching Hospital - Babatunde O. Bamgbose; Zahrau S. Abdu; Olajumoke Enahoro; George Ewansiha; Anas I. Yahaya; Edugie Ekuase; Auwal S. Balarabe; Junichi Asaumi (Journal of Dentomaxillofacial Science, 2019)
Objective: Supernumerary teeth, also called fourth molar, in the mandibular molar region is a rare clinical finding. The reported prevalence of supernumerary teeth is 1.5-3.5% in the permanent dentition and 0.3-0.6% in the deciduous dentition. The supernumerary molars can be divided into two types: distomolars and paramolars.Methods: A 23-year-old female patient presented with symptoms of pericoronitis associated with an unerupted mandibular third molar at the Oral Diagnosis Clinic of the Aminu Kano Teaching Hospital. Periapical radiograph revealed an incidental finding of mandibular distomolar in the region of the left unerupted mandibular third molar.Results: This paper reports an unusual case of mandibular distomolar, incidence and prevalence, etiologic factors and management of mandibular distomolars.Conclusion: Distomolars are a rare clinical finding and are often impacted and located in the maxilla.